PERTUMBUHAN DAN PERKEMBANGAN CACING Perionyx excavatus PADA MEDIA VERMIKOMPOS UNTUK PENYUSUNAN E-MODUL MATERI PERTUMBUHAN DAN PERKEMBANGAN - Utami, Putri Intan; Muhfahroyin; Suharno Zen (EDUBIOLOCK, 2025)
The aims of this research are 1) to determine the effect of vermicompost media on the growth and development of Perionyx excavatus worms, 2) to determine the best dose of vermicompost media for the growth and development of Perionyx excavatus worms and 3) to determine whether or not the results of this research are suitable for use as a learning resource in the form of an E-Module in growth and development material. This type of research is quantitative using a Completely Randomized Design (CRD) with 20 samples. This study contained 1 control and 3 treatments with 5 replications. Control (100% media variation) and 3 treatments providing different doses of vermicompost media, P1 (75% vermicompost + 25% media variation), P2 (25% vermicompost + 75% media variation), P3 (100% vermicompost). The parameters observed in this study were the growth in weight of the worms and the number of worm cocoons. Data were analyzed using the Liliefors test, Hypothesis test and continued with the Honestly Significant Difference (BNJ) test. Based on the research results, there was an effect of dosing vermicompost media on the weight growth of worms. The results of the hypothesis test showed Fcalculated > Fcritical daf. While on the parameter of the number of cocoons, the dosage of vermicompost media did not give a significant effect. The results of the hypothesis test showed Fcalculated < Fcritical. Further BNJ testing showed that the P1 treatment gave the best effect on the growth and development of Perionyx excavatus worms. Based on the validation analysis of learning resources, this research has the potential to become a learning resource in the form of an E-module on Growth and Development material.